PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS INKUIRI TERBIMBING PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Dhea Novi Adelliani; Eny Enawaty; Rachmat Sahputra; Hairida .; Lukman Hadi (Jurnal Education and Development, 2022)
According to the observation that had been done before, it can be concluded that there was lack of attractiveness of LKPD, and learning by using lecture method made students less active while teaching and learning process. Thus, the researcher upgrading such as LKPD development that has learning method in form of guided inquiry. The purpose of this study is to implement LKPD towards guided inquiry that suitable to use and find out teacher’s respond. The methodology that used in this research is Research and Development by applying ADDIE model, but it has been determined to ADD that is Analysis, Design, and Development. In this research, the subject of the research is LKPD and the object is the teacher. The instrument to collect the data is language feasibility assessment sheets, materials, graphs and questionnaires for teacher’s respond. Moreover, the result after analyzing the data by carried out on expert validation of materials, graphics and language respectively are 94%, 94%, and 91% with very decent category. Therefore, the result of teacher’s respond that collected from questionnaire on LKPD that has been developed by using guided inquiry, shown the percentage is 80%. It is very feasible to be applied as a supplement in chemistry teaching and learning process.